Voices and values in shaping the subjectivity of pedagogical content knowledge - (:unkn) unknown (TAYLOR & FRANCIS AS, 2017)
Pedagogical content knowledge involves subjective decisions on the parts of teachers in making the content comprehensible to learners. This paper is concerned with the formation of this subjectivity and asks: how do (pre-service) teachers come to know and decide upon the best approach to making the content instructional for learners? In answering this question, this study draws upon data obtained from one pre-service mathematics teacher's microteaching and retrospective interviews. The data were examined through the lenses of the Bakhtinian notion of voice. The findings suggest that the pre-service teacher's understanding of pedagogy is formed and transformed, to an important extent, by the voices of others who are not necessarily physically present within the immediate instructional setting and who might be distant in space and time. Assimilation of those voices enacts particular value judgments, which in turn shapes and hence forms the subjectivity of the pre-service teacher's pedagogical practices.
Keywords: Bakhtin; mathematics teachers; pedagogical content knowledge; subjectivity; value; voice; SCIENCE TEACHERS BELIEFS; MATHEMATICS INSTRUCTION; STUDENT-TEACHERS; REFORM